THE VOICES OF THE MINOR CHARACTERS IN GEORGE ORWELL’S ANIMAL FARM - Edi, Shahrunif Binti; Mustikawati, Yunitari; Nur, Riola Haya (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
The perception of minor characters needed to be understood through their voices specifically in Animal Farm by George Orwell. Animal Farm contains the power gap that causes injustice to the minor characters. The purpose of this study is to investigate the characteristic elements of dialogue among the minor characters and the characteristics of the government system that are reflected in Animal Farm by George Orwell. In analyzing the voices of the minor characters, the theory is used by the Bakhtin theory of dialogism. Meanwhile, in analyzing the government system that reflected in Animal Farm used the theory of totalitarianism by Friedrich and Brzezinski. This study also used a qualitative method. In this study, the characteristic elements of dialogue are divided into two; discourse of authority and internally persuasive discourse. Discourse of authority consists of monological communication and hallmark. Internally persuasive discourse consists of dialogical communication which has empathy, beliefs, ideas, awareness, and confusion characteristics. Meanwhile the government system that is reflected in Animal Farm is similar to totalitarianism which fits into its six characteristics; official ideology, single party, terroristic police control, monopoly system related to communication, party’s monopoly related to opposition, and economic central control. This study definitively answers the questions regarding the characteristic elements of dialogue among the minor characters and the characteristics of totalitarianism as the government system that is reflected in Animal Farm.